Nondestructive Evaluation of Compound Layer on Nitrocarburized Steel - Zemmouri, Mohammad Noor (My University, 2019)
In industry, the evaluation of process quality is a crucial component for providing up-to-task final components. The heat treatment services over steel components are no exception to that rule. Therefore, companies tend to give close attention to this final assessment. In fact, such a step would determine the quality of the final component studied along that of the process. In order to achieve such an assessment, companies tend to use conventional metallographic methods which seem to give an accurate insight over the properties of the studied component. However, these destructive ways provoke long lead times, a lot of scrap and a respective waste of money. Therefore, the use of a nondestructive evaluation seems like an attractive idea, as it would allow reducing all the inconveniences mentioned before. Initially, this report includes a theoretical study about both nitriding processes and eddy current as a nondestructive evaluation technique of choice. Moreover, the study aimed at understanding the working principle of an already-deployed eddy current instrument. Consequently, the nondestructive equipment was used on a carefully chosen test matrix of steel samples. The main goal was to determine the compound layer thickness formed on top of several nitrocarburized steel components under different conditions. Eventually, these nondestructive evaluation values were compared to those of a metallographic study. Finally, the amount of information acquired from the literature survey and the nondestructive measurements was deployed to find other eddy current equipment suitable for the aforementioned application. The results obtained from the experimental procedures allowed a better understanding of the working principle of eddy current as a nondestructive thickness measurement device. Also, the impact of several parameters over the compound layer thickness and porosity levels was determined. For instance, one cannot use different steel grades to determine their compound layer thickness with the same eddy current calibration. On the other hand, the porosity levels affect directly the accuracy of eddy current readings. Finally, finding a perfectly suited new eddy current instrument for compound layer thickness measurement was discovered to be somewhat complicated; as the existence of a nondestructive equipment with such application was deemed scarce.
Keywords: Nitrocarburizing, Compound layer thickness, Nondestructive evaluation; Eddy current, Frequency, Measurement methodology, Metallographic method, Porosity level